Estimation of firing temperature and ancient geomagnetic field intensity of archaeological potteries recently excavated from Tamilnadu, India - Velraj, G.; Musthafa, A. Mohamed; Janaki, K.; Deenadayalan, K.; Basavaiah, N. (My University, 2010)
In the present study, fragmented pottery samples were collected from the recently excavated archaeological site named Salamankuppam near the famous Mahabalipuram in Chennai, Tamilnadu, India. An attempt was made to subject the samples to scanning electron microscope with energy dispersive spectrometer (SEM/ EDS) and chemical analysis. Also porosimetry study was done. The result from the analysis provided the chemical composition of the potteries, the firing atmosphere and firing temperature achieved by the artisans at the time of manufacture. The results obtained from different analytical techniques provided information of the firing temperature of the pottery which lies in the range of 800 °C–950 °C in the oxidizing and reducing atmosphere. Mineral magnetic studies also were performed and proved that all samples were highly magnetically enhanced materials and paleointensity measurements by Thellier method yielded the field intensity value of 42.15±2.0 μT. The age of the sample was around 150 BC.
Keywords: SEM-EDS; Firing temperature; Paleointensity; Pottery shreds; Porosimetry; Tamil Nadu; Chennai; Salamankuppam